UNCTAD XIII : Doha mandate and Doha Manar (UN New YorkUS, 2012)
Contains the text of both the Doha mandate which spells out the key challenges facing developing countries and the policies required, at global as well as national levels, to address them; and the Doha Manar, a pledge by all member States to work for a more development-oriented and inclusive globalisation.
Keywords: TRADE NEGOTIATIONS